Endangered languages of the Caucasus and beyond - Korkmaz, Ramazan, 1962-; Doğan, Gürkan (Languages of Asia series, 2017)
According to UNESCO, it is believed that at least half of the nearly 7,000 languages spoken around the world will cease to be used within the next 100 years. If this issue is neglected, people will lose not only their cultural heritage but also invaluable understandings about the history of all humankind. 'Endangered Languages of the Caucasus and Beyond' includes the manuscripts of 19 papers that were presented at the 1st International CUA Conference on Endangered Languages, organized by the Caucasus University Association (CUA), at Ardahan, Turkey, on 13 to 16 October 2014. The articles address issues such as the state of the field of documentation, conservation and revitalization of endangered languages with special reference to the endangered languages in the Caucasus region and beyond.